PENGARUH PENERAPAN PENDEKATAN PROSES TERHADAP KETERAMPILAN MENULIS KARANGAN NARASI SISWA SDN 17 SUNGAI RAYA - Veridiana, Veridiana; Halidjah, Siti; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to analyze the influence of process approach in narrative writing skills for Grade V at Elementary School 17 Sungai Raya Kabupaten Kubu Raya. Experimental method design in this research is Quasi Experimental with Nonequivalent Control Group Design. The research sample consisted of V B class as the control group and V C class as the experimental group selected by simple random sampling technique. Observation sheet and deeds test were used to collect data. Based on the data analysis, the result of average post-test of experimental class is 77,82 and post-test of control class is 72,33, tcount 2,128 and ttable (? = 5% and dk = 17 + 21 - 2 = 36) of 2.029, tcount> ttable. It can be concluded that there is the influence of process approach in narrative writing skills for Grade V at Elementary School 17 Sungai Raya Kabupaten Kubu Raya. The effect size calculation obtained ES = 0.68, including medium criterion, that is 0,2> ES 0,8. It can be said that the process approach gives a good influence in narrative writing skills for Grade V at Elementary School 17 Sungai Raya Kabupaten Kubu Raya. Keywords: Influence, Process Approach, Narrative Writing Skills.